Talking Point – Flexible Targeted Online Staff Development that Works - Campbell, Anne (Journal of Interactive Media in Education, 2016)
The UK Open University has a large, highly distributed workforce, particularly within its part-time teaching staff who work mainly from home and who live across the UK and Ireland. In these circumstances it is a challenge to provide professional development which allows for situated learning, peer interaction and community building. In this paper we describe a case study of an online initiative which allows distance staff easily to participate in one-day professional development events focussing on specific topics of relevance to particular groups. Event design incorporates a combination of near-synchronous sessions, synchronous sessions and web-based content. The short duration of the event enhances a sense of presence and can help to create an intense and stimulating development experience. A particular advantage of the design is in providing space which can be used to encourage informal situated learning, peer interaction and community building. The format also can easily bring together a diverse range of colleagues across geographic or subject boundaries. We describe and evaluate three different types of event which have run in this space, showing that the online format encouraged attendance, and the design afforded opportunities for peer engagement, reflection and social learning. The main drawback was the large message base in the event forum, which we mitigated by providing summaries of the discussion topics. Keywords: Professional development, Online learning, Distance learning, Social learning, Community building, Part-time staff